Lipase-initiated one-pot synthesis of spirooxazino derivatives: redesign of multicomponent reactions to expand substrates scope and application potential. Issue 23 (9th June 2016) - Chen, Xiao-Yang; Wang, Jun-Liang; Lin, Xian-Fu; Wu, Qi
Abstract: Enzymatic multicomponent reactions (MCR) are very powerful for complex organic synthesis with environmentally friendly, highly efficient and selective characters, while sometimes having some unavoidable shortages such as narrow substrate scope and so on. Herein, this work demonstrated how to redesign one previously reported lipase-catalyzed MCR to achieve more broad substrates and more efficient synthesis. Twelve new spirooxazino derivatives with different substitutions were obtained in moderate to good yield, while all of them could not be synthesized using the previous route. Reaction conditions such as enzymes, enzyme concentration, amides and ratio of substrates were screened. Furthermore, particularly interesting is that chiral spirooxazino could also be obtained through a further developed two-enzymatic MCR process in one pot. As a domino process simultaneously constructing six new C-C/N bonds and two rings in only one step, the work will remarkably expand the application scope of enzymatic MCR for simple and green synthesis of complex compounds. Graphical abstract: